Tres gramáticas olvidadas para enseñar español a italianos: Fabre (1626), Perles y Campos (1689) y Chirchmair (1709) - SÁEZ RIVERA, Daniel M. (Cuadernos de Filología Italiana, 2010)
In the 17th century Italy Lorenzo Franciosini was the main figure in the sphere of the teaching of the Spanish language, with his great works, which consist of grammars, vocabularies, translations and some other pieces. His influence reaches the 19th century. However, at least in the 17th century and in the beginning of the 18th century, some few teachers of languages, not really well known nowadays, dared to compete with him. In this paper we will analyze the works of these authors: Antoine Fabre (1626), Josef Faustino Perles y Campos (1689) y Mattia Chirchmair (1709)